PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUASAN NASABAH PADA KOPERASI MAKMUR AL KAUSAR PAMULANG - Mahmudi Mahmudi; Senen Senen; H Hastono (Jurnal Manajemen & Pendidikan [JUMANDIK], 2026)
This study aims to explore and comprehensively understand the influence of service quality and promotion on member satisfaction at Koperasi Makmur Al Kausar Pamulang through the direct experiential perspectives of active members. Cooperatives as community-based financial institutions play a strategic role in strengthening financial inclusion for lower-middle-income communities, yet the challenge of maintaining member satisfaction amid increasing competition from formal financial institutions has become increasingly pressing. This study employs a qualitative approach with a descriptive phenomenological design, involving 15 informants who are active members of Koperasi Makmur Al Kausar Pamulang with a minimum membership duration of one year. Data were collected through semi-structured in-depth interviews, participatory observation, and documentation, subsequently analyzed using inductive thematic analysis. The findings identify four main themes describing the dynamics of member satisfaction: (1) perceptions of staff responsiveness and empathy as the most influential service quality dimension; (2) accuracy of promotional information as a trust determinant; (3) gaps between service expectations and reality as sources of dissatisfaction; and (4) trust-based social relations as the cooperative's competitive advantage over formal financial institutions. This study contributes to a more contextualist understanding of cooperative member satisfaction in suburban urban environments such as Pamulang, while providing evidence-based recommendations for cooperative management to enhance service quality and promotional strategy effectiveness.